PENGEMBANGAN LKS TEMATIK BERBASIS KOMIK PADA MATA PELAJARAN IPA DI SMP - Zulfa Lusiana; Sri Wahyuni; Pramudya Dwi Aristya Putra (FKIP Universitas Jember, 2017)
This study was aimed at describing: (1) the validity of comic-based thematic worksheet, (2) students performance assessment while used comic-based thematic worksheet and (3) students responses after used comic-based thematic worksheet. This study was development research of 4-D method (define, design, develop, disseminate). The subjects of this study were students of class VII MTs Bustanul Ulum, Panti, Jember. The validity was assessed by user experts validator and audience related to feasibility of the content, language, presentation and graphic. The instruments used are sheets of worksheet validation, sheets of student performance assessment and sheets of student responses. The results showed that: (1) comic-based thematic worksheet classified as valid which has proven by qualitatively and quantitatively, (2) Students performance while used comic-based thematic comic is 83,19% and classified as excellent, (3) students responses was very positive showed that students feel happy, know, understand and attracted to the comic-based thematic worksheet. Keywords: thematic worksheet, performance assessment, students responses